Development of Photomyxotrophic Culture Protocol of Lemongrass Through Sucrose Concentration Increase and Light Intensity Decrease - Desy Irmawati; Enni Suwarsi Rahayu (Biosaintifika: Journal of Biology & Biology Education, 2023)
Lemongrass (Cymbopogon nardus (L.) Randle) plantlets are interesting to be used as tissue culture-based souvenir. The success of plantlet propagation through photomyxotrophic culture is influenced by several factors, including sucrose concentration and light intensity. The research aimed to analyze the effect of sucrose concentration and light intensity on the growth of lemongrass plantlets. This experimental research used randomized block factorial design with two factors, namely sucrose concentration (0 g/l, 10 g/l, 20 g/l, 30 g/l) and light intensity (2000 lux, 3000 lux, 4000 lux, 5000 lux). The variables observed were some parameters of growth and development of plantlet. The data were analyzed with two-way Analyses of Variance and Duncan Multiple Range Test. The results showed that sucrose concentration had significant effect on the number of shoots and leaves of plantlet. The light intensity and the interaction of both factors had also significant effect on the number of shoots and leaves. The most optimal treatments were sucrose of 20 g/l and light intensity of 3000 lux.  The results of this study innovate the tissue culture technique using photomyxotrophic system in order to produce sterile lemongrass plantlets in large quantities.